Tumbling object deorbiting using spaceborne laser engagement – A CubeSat case study. Issue 7 (1st April 2020) - Yang, Yang; Klein, Erik; Sagnières, Luc
Highlights: A high-fidelity attitude-orbit propagator tool is developed. A beam approach is used for surface interaction modelling. A tumbling 3U CubeSat has been lowered by its perigee height after laser engagement. The laser engagement becomes more effective with a faster initial rotational speed. Abstract: This paper demonstrates active space debris removal using spaceborne laser systems. The laser beam and the surface of the target are discretised into multiple rays and finite elements, respectively, for laser-target interaction modelling, in which the laser ablation process is investigated. A high-fidelity attitude/orbit propagator tool is developed to account for both the linear impulse and angular impulse induced by the laser engagement and other perturbations. The laser system is activated only when three switch criteria are satisfied. In numerical simulations, laser pulses from international space station are generated to deorbit a 3U CubeSat with initially tumbling modes. The results validate the effectiveness of deorbiting tumbling CubeSats using spaceborne laser engagement, with the perigee height lowered by approximately 2.4 km in around 30 min after 2 h propagation. It is also found that the laser engagement becomes more effective for an initially faster rotating object.